Spasmolytic effect of Vitis vinifera leaf extract on rat trachea - MK Gharib Naseri; A Heidari (Institue of Medicinal Plants, ACECR, 2006)
Background: Many reports have shown the various pharmacolosical effects for grape (Vitis vinifera) seed extract for instance: antioxidant, hypotensive and hypolipidemic and vasodilatory effects. We have recently shown the relaxatory effect of grape leaf extract on rat ileum, uterus, aorta and reducing the rate and contractility in frog isolated heart. Objective: The aim of present study was to investigate the effect of Vitis vinifera leaf hydroalcoholic extract (VLHE) on isolated rat tracheal contractions induced by KCl and acetylcholine. Methods: The trachea was removed from male adult Sprague Dalwey rat and placed in an organ bath containing Krebs-Henseleit solution. The tracheal contractions were recorded isometrically under 1.5g initial tension. Results: The results demonstrate that the VLHE at 0.5, 1, 2, 4 and 8 mg/ml reduces the tracheal contractions induced by KCl (60 mM) significantly and dose-dependently (P<0.0001). Acetylchline (55 μM)- induced tracheal contractions were also attenuated by the same extract doses significantly (P<0.0001). The VHLE-induced relaxation in the KCl-induced contraction in trachea was not affected niether by nitric oxide synthase inhibitor (L-NAME, 100 μM) or beta-adrenoceptor antagonist (propranolol 1 μM) and by moscarinic receptors antagonist (atropine 30 μM). Conclusion: These results suggest that the relaxant effect of VHLE on rat trachea is evoked via voltage dependent calcium channel blockage and beta-adrenoceptors, NO and cholinergic receptors are not involved in this relaxant effect of VHLE